PENGARUH EDUKASI KONSUMSI TABLET TAMBAH DARAH MELALUI MEDIA VIDEO TERHADAP PENGETAHUAN PENCEGAHAN ANEMIA PADA CALON PENGANTIN DI KUA KECAMATAN PANCORAN TAHUN 2022 - Alsa Safitri (2022)
Iron tablets is a nutritional supplement that is given to prevent anemia. In 2018, women at childbearing age who consumed the supplement as recommended was only 1.4%. The low consumption of iron tablets was caused by several factors, such as boredom, laziness, and bad smell. Beside that, there were also excuses like feeling nausea, vomiting, feeling pain in the epigastrium, as well as the dark colored urine which made women uneager to consume the supplement. The aim of this study is to find the influence of health education about iron tablet consumption to prevent anemia toward the knowledge of the prospective bride and groom in Pancoran Religious Affairs Office, Jakarta. This study used pre-experimental design with a pretest-posttest design without comparison (control). The number of the sample in this study was 154 respondents, by applying purposive sampling technique through collecting data by using questionnaires as well as health education media in a form of video. The result showed that the implementation of health education through video gave an influence on the increase of knowledge of the prospective bride and groom (p=0.000). It can be concluded that there was a difference of acknowledgement of theirs, before and after the health education through video in the Pancoran Religious Affairs Office. In order to prepare the needs of iron to create a good quality generation, it is important for the prospective bride and groom to have knowledge about the iron tablets and anemia. Keywords: Anemia, Health, Iron Tablets, Prospective Bride and Groom, Video